Responses of Pygoscelis adeliae and P. papua populations to environmental changes at Isla 25 de Mayo (King George Island) - Carlini, Alejandro R.; Coria, Néstor Rubén; Santos, Maria Mercedes; Negrete, Javier; Juares, Mariana Alejandra; Daneri, Gustavo Adolfo (Polar Biology)
As part of a monitoring study of Adélie and Gentoo penguin colonies, birds occupying nests with eggsand chicks in crèches were counted annually from the 1995/1996 to the 2006/2007 seasons at Stranger Point, Isla 25 de Mayo (King George Island), Antarctica. During the study period the Adélie penguin population showed a decrease of 62%. The number of chicks in crèches followed a similar trend, the smallest number occurring in 2002, when it was 63% lower than in 1995/1996. In contrast, the Gentoo breeding population size increased by 68%, while chicks produced increased by 63%. Despite the opposing trends in population size between species, there was a positive relation in their interannual variation, although the extent, and for some years the direction, of the change observed always favoured Gentoo penguins. Breeding success (chicks in cre`ches/nests with eggs) fluctuated between 0.65 and 1.26 for Ade´lies and between 0.76 and 1.27 for Gentoo penguins, and did not differ significantly between species. The similar breeding success of these species suggests that the contrasting population trends observed were driven by factors operating over winter. We suggest that current changes in environmental conditions may affect adult birds of both species during the previous winter with different intensity but in a roughly similar way, but that juvenile survival of both species and thus the recruitment of new breeders might be affected differentially, with a much lower survival rate of juvenile Adélie penguins. Fil: Carlini, Alejandro R. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Coria, Néstor Rubén. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Santos, Maria Mercedes. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del ...